2017
DOI: 10.24017/science.2017.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile and Antibacterial Sensitivity Patterns of Isolates among Burn Patients in Sulaimani City

Abstract: Resistance to antibiotics is rapidly increasing in our community and burn wounds are frequently infected by these multidrug resistant organisms. Careful antibiotic selection and effective control of these strains can be translated into lower morbidity and mortality for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…In our study, the most frequent isolated bacteria in the dead-cases was Acinetobacterbaumannii which presence (16.7%) in the single isolated bacteria, followed by Pseudomonas aeruginosa which present (6.7%) of the single isolated bacteria. These results were corresponded to a study by [15] in Iraq that revealed 90 samples were taken from patients in 2 hospitals in Baghdad city and the results was 65 samples (72.2%) were Acinetobacterbaumannii and the remain samples were the other microorganisms, and a study by [16] in Turkey which was a 3-years record at Van Training and Research Hospital in Van. The total number of bacterial isolates was 250 from 179 patients, the Acinetobacterbaumannii was (23.6%), after it coagulase negative Staphylococci (13%.6), and then Pseudomonas aeruginosa (12%), Staphylococcus aureus (11.2%) and Escherichia coli (10%).…”
Section: Discussionsupporting
confidence: 83%
“…In our study, the most frequent isolated bacteria in the dead-cases was Acinetobacterbaumannii which presence (16.7%) in the single isolated bacteria, followed by Pseudomonas aeruginosa which present (6.7%) of the single isolated bacteria. These results were corresponded to a study by [15] in Iraq that revealed 90 samples were taken from patients in 2 hospitals in Baghdad city and the results was 65 samples (72.2%) were Acinetobacterbaumannii and the remain samples were the other microorganisms, and a study by [16] in Turkey which was a 3-years record at Van Training and Research Hospital in Van. The total number of bacterial isolates was 250 from 179 patients, the Acinetobacterbaumannii was (23.6%), after it coagulase negative Staphylococci (13%.6), and then Pseudomonas aeruginosa (12%), Staphylococcus aureus (11.2%) and Escherichia coli (10%).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, aztreonam, amikacin and These bacterial pathogens arecreating from the urogenital and gastrointestinal tracts or from upper respiratory system add to the hospital condition and environmental contamination. In this study, the average of bacterial resistance was very highagainstselected antibiotics, the approach results are documented byRashid K et al (16) in our country. High resistance rate of antibiotics by Gram-negative bacilli isolates may be due to widespread drug-resistant bacteria or self-medication.Gurunathan S et al (7)studied the antibacterial activity of silver nanoparticles in combination with differentantibiotics "tetracycline,erythromycin, chloramphenicol, gentamicin, and vancomycin" againstGram-positive and Gramnegative bacterialpathogens, and they found strong synergisticbactericidal effect ofAgNPswhen combined withconventional antibiotics against : Gram positive and Gram-negativebacteria "StreptococcuspneumoniaeStaphylococcus aureus,Shigellaflexneriand…”
Section: Sample Collection and Bacterial Identificationsupporting
confidence: 77%
“…Moreover, P. aeruginosa is known to form a biofilm that gives long survival benefits and prevents eradication by the immune system of the host or antibacterial treatment (Thi et al, 2020). Among the eligible studies, S. aureus was the first pathogen of infection among burn patients in 5 studies (Cen et al, 2015;Li et al, 2018;Chen et al, 2021;Rashid et al, 2017;Basit et al, 2021) , and the second pathogen in three studies (Kulkarni et ., 2015;Chaudhary et al, 2019;Asena et al, 2020). In general, S. Aureus has variant pathogenicity factors that assist host tissue adhesion, immune system response evading, and apoptosis, such as coagulase enzyme, surface protein, and toxins (Issler-Fisher et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A. baumannii also was recorded as the first pathogen of infection among hospitalized burn patients in three studies (Wang et al, 2014;ALfadli et al, 2018;Yolbaş et al, 2013), while it was the second pathogen in six studies (Cen et al, 2015;Li et al, 2018;Wardhana et al, 2014;Haghighifar and KamaliDolatabadi, 2020;Rashid et al, 2017;Hamed et al, 2016). A. baumannii is considered a part of human normal skin flora, and can survive in the hospital environment for a long time because of its resistance to multiple antibiotics, the tendency to humidity, and the ability to cling to inanimate surfaces (Sharma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation